"But sex work is good but I don't want to do it": Black men's narrative of selling sex - Peters, Simone (Department of Psychology, 2018)
Sex work within the South African context has become a much contested issue; with different perspectives emerging on the topic from various stakeholders. Sex work in South Africa, takes place in a complex context of poverty and lack of jobs, which plays a part in men's entry into the profession. While much research has been done on sex work, it has tended to focus on female sex workers, to the detriment of male sex workers. Male sex workers have been made invisible in the literature on sex work and their experiences are thus not adequately presented. This research however hopes to gain insight into Black men's experiences of sex work in Cape Town. Narrative interviews were used to investigate the experiences of 16 black male sex workers, from SWEAT, a Cape Town based NGO. All the interviews were analysed using a combination of an intersectional and narrative approach, to best understand the complexities and different factors that shape their lived experiences. Through this analysis, many complexities and tensions within male sex workers' experiences were found. Their experiences of entry and exit from sex work have and continue to be shaped by their race, age, socio economic status and gender. As men in this profession, they encounter many challenges and judgement, however being a man has also provided them with advantages not afforded to female sex workers. These findings are then discussed in relation to the existing literature and recommendations for future research and interventions are offered.